Profil Kadar Glukosa Darah Puasa dengan dan Tanpa Minum Air Putih - Karenima Eka Wahyu Nurrois (Jaringan Laboratorium Medis, 2022)
Blood glucose levels are influenced by factors related to pastients and laboratory factors. There are various ways to treat blood glucose that have increased or decreased. Water consumption helps the process of removing all toxins in the body, including excess sugar. In James’s research (2010), that drinking water causes a breakdown of sugar. This research is to Know the description of fasting blood glucose levels with and without drinking water. Descriptive type research with cross sectional approach. Blood glucose levels of 28 student of TLM was examined by POCT methode and the respondent filled out the questionnare. The results of blood glucose levels are described based on questionnares that have been filled in the form of respondents diagram. From the results of examination 28 respondents, mean blood glucose level in conditions without drinking is 82,03 mg/dl, respondents with a minimum level of 65 mg/dl and a maximum of 97 mg/dl. Mean blood glucose level in conditions with drinking is 78,71 mg/dl, respondents with minimum level of 69 mg/dl and maximum of 104 mg/dl. Respondent’s fasting blood glucose levels in conditions without drinking and drinking decreased by 4%. There was a decrease in fasting blood glucose levels in respondents conditions without drinking and by drinking water, also influenced by physical activity factors, nutrition intake, drugs/vitamin and obesity.